2016
DOI: 10.3390/ijms17101656
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamide Derivatives as Mammalian Arginase Inhibitors: Synthesis, Biological Evaluation and Molecular Docking

Abstract: Arginases are enzymes that are involved in many human diseases and have been targeted for new treatments. Here a series of cinnamides was designed, synthesized and evaluated in vitro and in silico for their inhibitory activity against mammalian arginase. Using a microassay on purified liver bovine arginase (b-ARG I), (E)-N-(2-phenylethyl)-3,4-dihydroxycinnamide, also named caffeic acid phenylamide (CAPA), was shown to be slightly more active than our natural reference inhibitor, chlorogenic acid (IC50 = 6.9 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 55 publications
1
25
0
1
Order By: Relevance
“…6 It contains some phenolic compound such as quercetin, 6 epicathecin, epicathecin galat, kaempferol 6,26 which is suspected as responsible compound for inhibitor of mamalia arginase 1 also cinnamic acid derivate 27 which can be also responsible for the inhibitory effect on arginase. 28 These compound worked synergistically in the extract and showed higher arginase inhibitory effect on arginase than other Part extract of the plant. In other study, flavonol and epicatechin from Cocoa showed inhibition of arginase in HUVEC, 29 Flavanone from Scutellaria indica showed inhibition of arginase in mice kidney lisate.…”
Section: Figure 1: Melastoma Malabathricum Leavesmentioning
confidence: 96%
“…6 It contains some phenolic compound such as quercetin, 6 epicathecin, epicathecin galat, kaempferol 6,26 which is suspected as responsible compound for inhibitor of mamalia arginase 1 also cinnamic acid derivate 27 which can be also responsible for the inhibitory effect on arginase. 28 These compound worked synergistically in the extract and showed higher arginase inhibitory effect on arginase than other Part extract of the plant. In other study, flavonol and epicatechin from Cocoa showed inhibition of arginase in HUVEC, 29 Flavanone from Scutellaria indica showed inhibition of arginase in mice kidney lisate.…”
Section: Figure 1: Melastoma Malabathricum Leavesmentioning
confidence: 96%
“…However, many of these prototypes have an unfavourable toxicological profile, with high potency (subnanomolar range), especially in relation to hepatocytes, which results in them being decharacterised as new inhibitors unless such obstacles are improved by means of structural, molecular, or pharmacotechnical modifications (prodrug and vector-based dosage forms). Furthermore, another issue to be addressed is the inappropriate (oral) pharmacokinetic profile presented by most of the available inhibitors, since in most cases these are substances whose structures are based on amino acids, which easily lose stability (very short half-life) and potency at physiological pH [121].…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…NO is a crucial vasoconstrictor. 9 Besides, excess of ornithine causes vascular structural problems and neural toxicity. 7 Also related to abnormal arginase activity, previous study showed that urea at certain concentrations can induce reactive oxygen species (ROS) production which further cause activation of pro-inflammatory pathways, and inactivation of the anti-atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibiting arginase activity has proven to be beneficially useful in various illness such as hypertension, erectile dysfunction, diabetic renal injury, myocardial ischemiareperfusion injury. 9 Arginase inhibitor is compounds that interact with arginase which reduce the activity of this enzyme and increase the availability of L-arginine as substrate for NOS resulting in NO balancing. First generation of arginase inhibitor is N-hydroxy-l-arginine (NOHA) and N-hydroxy-nor-l-arginine (nor-NOHA), characterized by N-hydroxy-guanidinium side chains.…”
Section: Introductionmentioning
confidence: 99%